Pengaruh Disiplin Kerja Dan Kompensasi Terhadap Produktivitas Kerja Karyawan Bagian Produksi Di Ssc Quality Tasikmalaya - Sobur Sobirin; Arga Sutrisna; Suci Putri Lestari (Jurnal Manajemen Riset Inovasi, 2023)
: This study aims to examine the effect of work discipline and compensation both simultaneously and partially on the work productivity of Production Section employees at SSC Quality Tasikmalaya. The population in this study is 45 respondents who are employees of the Production Department at SSC Quality Tasikmalaya. The data collection methods used are interviews and questionnaires. Data analysis techniques in this study using multiple linear regression analysis, correlation coefficient and coefficient of determination using SPSS software version 25. The results of this study indicate that work discipline and compensation simultaneously affect work productivity. Work discipline partially has a positive and significant effect on work productivity. Compensation partially has a positive but insignificant effect on work productivity.